Sharia Banking Performance Measurement Challenges - Indrasari, Meithiana; Purwadi, Ari; Zulkifli,; Nguyen, Phong Thanh; Mujanah, Siti (International Journal of Psychosocial Rehabilitation, 2020)
Execution assessment on Sharia budgetary foundations, particularly Sharia banks, intends to gauge the exhibition and strength of banks dependent on the recently set targets. This is done as a control to improve future execution by distinguishing inadequacies of Sharia banks activity consistently. Building the correct exhibition estimation appropriate with the attributes of an organization is a significant angle, particularly in a world unbounded, to stay serious and monetarily solid. As a bank that works dependent on Sharia values, there are sensible results in particular certain criteria that must be met in the operational procedure. There are in any event three components of execution that are significant attributes in the operational act of Sharia banks. To start with, Sharia banks in completing their activity, as a major aspect of the financial facet, are benefit situated. Notwithstanding, profit must be accomplished through tasks that hold fast to Sharia values.